Fermentation of vinegar from star fruit (averrhoa carambola) - Abdul Karim, Mohamed Ismail; Jasni, Farah Izora; Jamal, Parveen (IIUM Press, 2011)
Fermentation of star fruit juice was conducted to produce vinegar using the yeast Saccharomyces cerevisiae and Acetobacter aceti bacteria. The acetic fermentation was carried out for 120 hours in shake flasks with ethanol concentration of 4, 6 and 8% (v/v), inoculums size of 6, 8 and 10% or ml (v/v) and agitation of 150, 200 and 250 rpm. Two level factorial designs from Design Expeli are applied for experimental design and analyses of acetic acid and ethanol were conducted using ANOVA analysis to select the optimized results. The experiment showed that the optimum conditions for acetic fermentation is with 8% (v/v) of ethanol and 10% inoculums (v/v) and 250 rpm agitation speed. The vinegar obtained had a concentration of acetic acid of 2.855% which was higher than predicted value obtained from the selected fennented star fruit juice and the efficiency of acetic fermentation was 32.5%.